Demonstrating the self-healing behaviour of some selected ceramics under combustion chamber conditions. (15th July 2016) - Farle, A; Boatemaa, L; Shen, L; Gövert, S; Kok, J B W; Bosch, M; Yoshioka, S; van der Zwaag, S; Sloof, W G
Abstract: Closure of surface cracks by self-healing of conventional and MAX phase ceramics under realistic turbulent combustion chamber conditions is presented. Three ceramics namely; Al2 O3, Ti2 AlC and Cr2 AlC are investigated. Healing was achieved in Al2 O3 by even dispersion of TiC particles throughout the matrix as the MAX phases, Ti2 AlC and Cr2 AlC exhibit intrinsic self-healing. Fully dense samples (>95%) were sintered by spark plasma sintering and damage was introduced by indentation, quenching and low perpendicular velocity impact methods. The samples were exposed to the oxidizing atmosphere in the post flame zone of a turbulent flame in a combustion chamber to heal at temperatures of approx. 1000 °C at low pO2 levels for 4 h. Full crack-gap closure was observed for cracks up to 20 mm in length and more than 10 μ m in width. The reaction products (healing agents) were analysed by scanning electron microscope, x-ray microanalysis and XRD. A semi-quantification of the healing showed that cracks in Al2 O3 /TiC composite (width 1 μ m and length 100 μ m) were fully filled with TiO2 . In Ti2 AlC large cracks were fully filled with a mixture of TiO2 and Al2 O3 . And in the Cr2 AlC, cracks of up to 1.0 μ m in width and more than 100 μ m in length were also completely filled with Al2 O3 .